POSITIVE POLITENESS STRATEGIES FOUND IN THE “BEAUTY AND THE BILLIONAIRE” MOVIE - Sukariyani, Ni Ketut; Maharani, Putu Devi (Universitas Muhammadiyah Makassar, 2025)
The concept of politeness is very important in human interaction, because it can foster harmonious communication and relationships. This research explores one type politeness strategy found in